Comparative study of antioxidant and anticancer activities and HPTLC quantification of rutin in white radish (Raphanus sativus L.) leaves and root extracts grown in Saudi Arabia - Noman Omar M. (De Gruyter, 2021)
The nutrient contents of Raphanus sativus L. (white radish) leaves (RSLs) and roots are known to have promising vital effects. We comparatively investigated the leaves and roots of R. sativus grown in Saudi Arabia to estimate the total phenol and flavonoid contents using the standard colorimetric methods. The antioxidant activity of RSLs and R. sativus roots (RSRs) were measured by 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays. Both extracts’ cytotoxic activity was assessed by MTT assay against several human cancer cell lines (A549, HepG2, MDA-MB-231, and MCF-7). High-performance thin-layer chromatography was used to identify and quantify the biomarker compound rutin in both extracts. The total phenolic content in RSLs (125.3 mg of gallic acid equivalent [GAE]/g) was higher than that in roots (95.8 of GAE/g), whereas the flavonoid content (44.5 mg of quercetin equivalent [QE]/g) was almost double compared in RSR extract (24.4 of QE/g). Similarly, RSLs exhibited a higher antioxidative activity than RSRs in both DPPH (IC50 216.8 vs 359.7 µg/mL) and ABTS (IC50 326.7 vs 549 µg/mL) models. RSLs also demonstrated the highest antiproliferative efficiency against all cell lines, with IC50 values of 217–453 µg/mL. The reversed-phase-high-performance thin-layer chromatography results showed the presence of rutin (5.2 µg/mg) only in RSLs. Our study indicates RSLs as a promising source of bioactive compounds compared with roots.